PELATIHAN PENGELOLAAN EMOSI PADA GURU UNTUK MENINGKATKAN KEBAHAGIAAN DALAM BEKERJA - Winta, Mulya Virgonita Iswindari; Kurnianingsih, Sri; Elfitasari, Tita (TEMATIK, 2021)
KB-TK Siti Sulaechah 04 is a school for early childhood. The problem that arises is that there are interpersonal and intrapersonal conflicts among teachers that cause stress that affects happiness at work. Emotional management training is needed. The ultimate goal of this training is that teachers are able to manage their emotions so that they can carry out their jobs happily.The methods used in this training are lectures, self-identification exercises, and discussions. In the lecture method, participants were given material to know about emotions, managing emotions, in self-identification exercises participants were invited to practice recognizing their emotions, expressing their emotions, modifying their emotions. The training ended with a discussion.The results show that participants can identify the sources of emotional causes, emotional expressions that are usually raised, how they feel, and the impact after expressing emotions. Participants were able to identify more precise emotional expressions and be able to predict the impact after modifying their emotional expressions. Participants can identify negative thoughts that usually accompany negative emotions and can identify positive thoughts that should be thought of, and their impact on themselves and others. Participants can identify actions/expressions of negative emotions that are usually taken and can identify more appropriate actions that should be taken, and their impact on themselves and others.Key words : Emotion Regulation Training, Happiness, Teacher